2023
DOI: 10.3390/w15030450
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Actual Evapotranspiration Using Satellite-Based Surface Energy Balance Derived from Landsat Imagery in Northern Thailand

Abstract: In this study, satellite-based measures of surface energy balance and the mapping evapotranspiration at high resolution with internalized calibration (METRIC) from Landsat imagery were used to estimate the spatiotemporal distribution of actual evapotranspiration (ETa) in northern Thailand, constituting a procedure that has rarely been performed in southeast Asia. Subsequently, we compared the ETa obtained from METRIC with that calculated using the FAO-56 dual-crop coefficient method via the SIMDualKc software … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
1
0
0
1
Order By: Relevance
“…The representation of ET data through imagery is significantly influenced by cloud conditions. It is also important to note that several previous studies conducted in Thailand have confirmed a strong correlation between ET image data obtained from Landsat 8 and numerical models during the dry season in the country (Suwanlertcharoen et al, 2023).…”
Section: Comparison Resultssupporting
confidence: 53%
“…The representation of ET data through imagery is significantly influenced by cloud conditions. It is also important to note that several previous studies conducted in Thailand have confirmed a strong correlation between ET image data obtained from Landsat 8 and numerical models during the dry season in the country (Suwanlertcharoen et al, 2023).…”
Section: Comparison Resultssupporting
confidence: 53%
“…Para la obtención del flujo de calor del suelo (G) se aplicaron la ecuación 4 y 5, que dependen del IAF (Suwanlertcharoen et al, 2023).…”
Section: Le = Rn -G -Hunclassified